Evaluation of the implementation of English medium instruction - Qomariah, Avdhikka Rayni; Driana, Elin; Setiadi, Hari (Jurnal Penelitian dan Evaluasi Pendidikan, 2022)
This study aimed to evaluate the implementation of the English medium instruction (EMI) program at Harapan Ibu Islamic Elementary School in the academic year of 2020/2021 by applying the CIPP model with a descriptive qualitative method. Data were gathered through interviews with stakeholders, observation of the teaching-learning process using EMI, and documentation. The results of the evaluation are as follows: the suitability of the program context to the expectations of stakeholders is considered very good. As seen from the information on the use of English as the medium of instruction, stakeholders know and agree with the program's implementation; the program's input is considered good. The program is regarded as good because it has adequate and good facilities, infrastructure, and standardized quality. The program's process is regarded as good, as indicated by the interaction between teachers and students using English as well as learning evaluations using English as the medium of instruction. The products of the program (output and outcome) are considered very good as shown by students' academic achievements above the minimum mastery criteria, students' non-academic achievements in the form of achievements in English language competitions, alumni's academic achievements in the form of their junior high school learning outcomes above the minimum mastery criteria, and the non-academic performance of the alumni in the form of ease of learning adjustment and their  confidence in junior high school.